Gerenciamento da manutenção produtiva total: proposta de implantação na Companhia Riograndense de Mineração - (:unkn) unknown (Universidade Federal do Pampa, 2015)
In an increasingly competitive landscape, companies seek to introduce new tools and methodologies in the management of their processes to make it possible to achieve high levels of efficiency and profitability. In this context, it arises the need for high availability of equipment. Moreover, there is the need to reduce operating costs, improve quality, safety and efficiency of facilities and equipment, and also the concern with environmental issues. To be able to achieve all these goals the maintenance is a key element, since it is no longer considered only as a cost-generating process to become an ally in the pursuit of excellence. Based on these needs, the article aims to apply the management of the maintenance process, using the methodology of Total Productive Maintenance (MPT), once the maintenance process is inserted at the strategic level of companies. The purpose of this article is to suggest a model of implementation of this methodology within a coal mining industry based on the state of Rio Grande do Sul, in the city of Candiota. To do so, a case study was developed, which consists of a qualitative research conducted by the application of interviews in some business sectors, in addition to the theoretical review of the MPT concepts and coal mining. At the end of the study it can be conclude that the methodology is applicable, but some difficulties may arise due to job descriptions and functions of employees.
Keywords: Engenharia; Engenharia de produção; Implantação; Manutenção produtiva; Gerenciamento; Mineradora; Mineradora de carvão; CNPQ::ENGENHARIAS